Effect of Fair Value Accounting and Corporate Governance on Stock Prices: Evidence of Information Efficiency in Thailand - Wonlop Writthym Buachoom (Advances in Pacific Basin business, economics and finance, 2022)
Abstract This chapter focuses on information efficiency as provided by fair value accounting (FVA) and corporate governance (CG) practices in an emerging market. Positive accounting theory was adopted as an empirical model to test the relationship between information efficiency and stock prices. Data for the period 2007–2020 from 576 listed firms on the Stock Exchange of Thailand were collected, tested, and analyzed using a fixed effect estimator. The results indicate that investors in the stock market trust the use of publicized efficient information as provided by FVA and CG practices in making their investment decisions, when FVA and CG proxies were found to significantly influence stock prices. Hence, this evidence implies that information efficiency leads to better firm values in an emerging market.
Keywords: Auditing, Earnings Management, Governance; Corporate Finance and Governance; Financial Reporting and Valuation Research